2003
DOI: 10.1183/09031936.03.00004503
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory markers in cystic fibrosis patients with transmissiblePseudomonas aeruginosa

Abstract: Chronic Pseudomonas aeruginosa infection in cystic fibrosis (CF) leads to a damaging host inflammatory response. There are an increasing number of reports of P. aeruginosa cross-infection at CF centres. The clinical significance of acquisition of a transmissible strain for patients who already harbour P. aeruginosa is unclear. In this study, levels of inflammatory markers in clinically stable adult CF patients who harbour transmissible and sporadic strains of P. aeruginosa have been compared.Patients with CF a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 28 publications
4
31
0
Order By: Relevance
“…However, none of these studies investigated the impact of phage-targeted pseudomonal killing on lung inflammation. This is highly relevant as persistent neutrophilic inflammation has been associated with lung injury (25) and, even during periods of stability, CF patients with chronic P. aeruginosa infection have higher inflammatory indices than subjects without CF (26). The reduction in the bacterial load demonstrated in previous studies does not necessarily equate to attenuation of inflammatory damage.…”
mentioning
confidence: 78%
“…However, none of these studies investigated the impact of phage-targeted pseudomonal killing on lung inflammation. This is highly relevant as persistent neutrophilic inflammation has been associated with lung injury (25) and, even during periods of stability, CF patients with chronic P. aeruginosa infection have higher inflammatory indices than subjects without CF (26). The reduction in the bacterial load demonstrated in previous studies does not necessarily equate to attenuation of inflammatory damage.…”
mentioning
confidence: 78%
“…Inflammatory markers have been compared between patients with sporadic P. aeruginosa and patients with the MES, showing that there was no significant difference between the two groups. This suggests that infection with the MES is not associated with a heightened inflammatory response [108]. However, there is evidence from the same CF centre that infection with a transmissible strain is associated with healthcare need and antibiotic usage [109].…”
Section: Other Uk Strainsmentioning
confidence: 97%
“…WOLTER et al [20] reported a significant effect on the "time trend" of C-reactive protein over the course of the study with a fall in the azithromycin group. However, this systemic measure of inflammation is not a valid predictor of the local inflammatory process in the airways [23]. SAIMAN et al [22] measured interleukin-8 and neutrophil elastase (both markers of inflammation in CF) in sputum and demonstrated no clinically significant difference between the groups at the end of the study period.…”
Section: Why Does It Work?mentioning
confidence: 99%